European Small Business Finance Outlook: June 2016 - Helmut Kraemer-Eis; Frank Lang; Wouter Torfs; Salome Gvetadze (European Investment Fund (EIF), 2016)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity, guarantees, securitisation, microfinance). It is an update of the ESBFO December 2015. We start by discussing the general market environment, then look at the main aspects of equity finance and the guarantees/SME Securitisation (SMESec) market. Finally, before we conclude, we briefly highlight important aspects of microfinance in Europe.
Keywords: 330